The Relevance Of Gender Studies In Deconstructing And Reconstructing Sustainable Development - Shuib, Rashidah (2016)
We are living in a complex, interconnected and a fast changing world. We have seen vast improvements in our lives. Generally people are living longer and are better educated. In many countries people have access to clean water, health care services, decent homes and food. We are connected by the internet in ways never imagined before. Yet inequity and inequality runs deep between and within countries. According to the United Nations (2016), in certain countries, income inequality has increased by 11 percent between 1990 and 2010. Unequal distribution of income is becoming a feature in many societies affecting more than 75 percent of the population. This situation is worse than in the 1990s. Certain countries and segments of the population are still beset by serious economic, political and social crises such as poverty, limited accessibility to essential medical/health care, high maternal mortality ratio, violence against women and child marriage which are all compounded by the impact of climate change, natural disasters, civil conflicts and wars. Pregnant women in the rural areas are more likely to die at birth compared to those in the urban areas.